Correlation of Students’ Listening Comprehension Score With Students’ Learning Styles at Students of English Department at University of Muhammadiyah Gresik - Hedar Pratama, Chico; Anwar, Khoirul (J-SHMIC : Journal of English for Academic, 2024)
Listening ability is an important component of language teaching and learning as it tends to improve faster than speaking ability and frequently influences skill development when learning anything new. Meanwhile, in order to accomplish excellent academic outcomes, students need to consider their learning styles and teachers need to consider various students’ learning style. This study aims to investigate the correlation between the listening abilities of learners and their learning styles. The participants were students of English education study program, faculty of teaching and educational sciences, Muhammadiyah University of Gresik, with 48 males and 52 female students participating. This study employed quantitative approaches using a questionnaire to assess students' learning styles, a test to assess students' listening comprehension scores, and an interview as a few sample about students’ perception. The data analyzed used SPSS Pearson's Correlation Coefficients and thematic analysis. The level of probability (p-value) significance (sig.2-tailed) resulted in .003. Since, the p-value (.003) was less than .05, Ha (alternative hypothesis) was accepted and Ho (null hypothesis) was rejected. As a result of the acceptance of the Ha (alternative hypothesis), researchers discovered there is a significant correlation connecting both visual and auditory learning styles and listening comprehension. The impact of this study to help students aware with their learning styles and teachers need to consider efficient learning activities with students’ various learning style.